1989
DOI: 10.1093/ajcn/49.3.457
|View full text |Cite
|
Sign up to set email alerts
|

Bile-salt-activated lipase: effect on kitten growth rate

Abstract: Because of the presence of bile-salt-activated lipase in cat milk, the dependence of the kitten on bile-salt-activated lipase is anticipated for milk fat absorption. To test this hypothesis, we initiated a feeding experiment comparing the growth rate of kittens fed with formula with those fed with formula and supplemented with purified human milk bile-salt-activated lipase. The results indicated that the kittens fed formula with supplemental enzyme had a growth rate twice that of kittens fed with formula alone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Fat excretion also decreased by 50% in low birth-weight infants when fed the diets containing CEL. Kittens were also found to gain 50% less weight when fed a formula without CEL instead of nursed littermates or littermates fed CEL-supplemented formula (73). In our studies with CEL-null mice, we found that pups nursed by CEL-null dams contained large amounts of tri-, di-, and mono-glycerides in their colon contents while none was detectable in pups nursed by control dams (74).…”
Section: Triglyceride Absorptionmentioning
confidence: 76%
“…Fat excretion also decreased by 50% in low birth-weight infants when fed the diets containing CEL. Kittens were also found to gain 50% less weight when fed a formula without CEL instead of nursed littermates or littermates fed CEL-supplemented formula (73). In our studies with CEL-null mice, we found that pups nursed by CEL-null dams contained large amounts of tri-, di-, and mono-glycerides in their colon contents while none was detectable in pups nursed by control dams (74).…”
Section: Triglyceride Absorptionmentioning
confidence: 76%
“…Bile-salt activated lipase is a component of cat milk, and evidence suggests that this plays a role in the fat digestion process of the new-born [29]. Its presence in cats' milk further suggests that pancreatic lipase levels are low in the new-born.…”
Section: Age and Digestibilitymentioning
confidence: 99%
“…Alternatively, the cat may display a similar type of lipolytic enzyme development to the pig: a non parallel pattern, suggested to reflect the importance of the different enzymes at the suckling and post-weaning phases (Tab. V) [10,25,29].…”
Section: Age and Digestibilitymentioning
confidence: 99%
“…BSSL is reported to withstand (dormant) the infant stomach pH, while resuming its activity in gastrointestinal areas where elevated levels of bile salt are available [39][40][41]. [42][43][44] Bile salts not only facilitate the adsorption of co-lipase and lipase, but also aid in the solubilization of the lipolysis products as they accumulate at the interface, into mixed micelles, allowing the transport to and through the gut mucosal surface [28]. The gut cell lining is then able to sense these nutrients and in response, secrete hormones and peptides that slow digestion and send signals to the brain that reduce appetite [45].…”
Section: Introductionmentioning
confidence: 99%